Study of thermoelectric power generator - Heng, Ri-Liang. (2011)
Thermoelectric power generation converts heat into electrical power. The thermoelectric effect was discovered back in the 1800s but has only gained significant interest in recent years due to technological advancements in the semiconductor industry and the need to find renewable sources of energy due to depleting fossil fuels. Despite this, thermoelectric power generators are not commercially viable due to the low efficiencies (electrical power output over heat input) of the materials. In the search for better thermoelectric materials, a clearer understanding of the impact of the various effects on the amount of heat input and electrical power output has to be established. In this project, a set of equations were proposed in a simulation model that considers the effects of Thomson heat and the temperature dependency of the other coefficients such as thermal conductance and Seebeck. The reliability of this model is verified experimentally by testing a commercially available bismuth telluride thermoelectric module with varying heat inputs in a vacuum chamber. The results of the simulation was relatively close to that of the experiments. The main reasons for the discrepancy was found to be the imperfect thermal contact and uneven heat distribution of the heater used.